Study on construction & demolition waste management in construction site - Mohd Faizul, Yusof (2006)
The Malaysia construction industry nowadays generates a large quantity of construction and demolition waste. Construction and demolition waste defined as a mixture of surplus materials arising from any excavation, civil or building construction, site clearance, demolition activities, road works, and building renovation. The disposal of construction and demolition waste at landfills has caused major environmental concerns and government sources indicate that there is an acute shortage of landfill space ion Malaysia. The aims of this study are to give background information on C&D waste problems in Malaysia and propose a practical guidance to building professional on how to manage and minimise C&D waste. Construction site waste management is not the major issues in construction site nowadays. But, with the new development of town and country, it probably will increase time to time and it is also effect directly into environmental issues. Further developments are recommended to develop a scientific methodology to quantify construction & demolition waste. Furthermore, more practical support is required to enforce the implantation of Construction & Demolition Waste management scheme in the construction and building field. It is also recommended to extend research on the area of recycling technique of building materials to conduct feasibility studies, including cost and payback period analysis for each technique.